Mathmatic Anxiety in Students at their First Year in Universidad Nacional de Costa Rica - Espinoza-González, Johan (2016)
This paper presents a research advance of a project that aims to study the levels of math anxiety having a group of students from Universidad Nacional de Costa Rica and establish its relationship with some variables such as gender, place of origin, academic performance, type of school where he obtained in high school, his course, repetition, etc. For this, an adaptation of mathematics anxiety scale Fennema-Sherman (1976), which has been validated over 30 years of application is used. Student interviews will be conducted to determine the factors that influence the behavior of their math anxiety. This study aims to provide new information on the influence of math anxiety in Costa Rican college students and the factors that influence levels of math anxiety and its relationship to academic performance.